Cervical Squamous Carcinomas With Prominent Acantholysis and Areas Resembling Breast Lobular Carcinoma: An Aggressive Form of Dedifferentation. (January 2018) - Scott, Kerry; Bryson, Gareth; Jamison, Jackie; Coutts, Michael; McCluggage, W. Glenn
Abstract : There have been occasional reports of primary cervical adenocarcinoma with areas of dedifferentiation resulting in morphologic mimicry of breast lobular carcinoma. We describe 4 cases of primary cervical squamous carcinoma with prominent acantholysis (3 cases), areas resembling breast lobular carcinoma (3 cases) or both (2 cases). All 4 tumors showed positivity with p63 and CK5/6 and 3 of 4 exhibited block-type immunoreactivity with p16. Two of the 4 cases contained high-risk human papillomavirus (types 16 and 18) on molecular testing; of the 2 cases which were human papillomavirus negative, 1 exhibited patchy nonblock immunoreactivity with p16. All cases exhibited some degree of loss of E-cadherin membranous staining in the areas of acantholysis and foci resembling breast lobular carcinoma. Three of 4 patients had extracervical spread at diagnosis; the fourth patient developed extracervical recurrence on follow-up. The initial FIGO stages were IB1, IIB (2 cases) and IVB. The 2 patients whose neoplasms were human papillomavirus negative developed distant metastases (supraclavicular, meningeal, and lung) during the course of their disease; the same 2 patients died of disease at periods of 4 mo and 1 yr after diagnosis. Cervical squamous carcinomas with acantholytic features and areas resembling breast lobular carcinoma are an unusual morphologic variant of squamous carcinoma. We consider the acantholysis and mimicry of breast lobular carcinoma to be part of a spectrum of morphologic changes, possibly related to loss of E-cadherin. These features can be regarded as a form of dedifferentiation which indicates a potential for aggressive behavior.